Social Accountability: Introducing a new dimension in optometric education - Moodley, VR; Loughman, J; Naidoo, KS (South African Journal of Higher Education, 2016)
Optometry globally has undergone major developments yet poor eye health statistics remain. The World Health Organization (WHO) cites social accountability as key to addressing health challenges, urging the education sector to be more socially accountable and train according to the needs of society. A qualitative, descriptive study was used to determine the integration of social accountability within optometric education in sub-Saharan Africa. Eleven academic leaders and two student groups participated in key stakeholder interviews and focus group discussions respectively. Data was thematically analysed using interpretive content analysis. The study found that social accountability policies or practices were not formally integrated across any academic area in the represented optometry education programmes. Optometric education needs to embrace and implement social accountability at country, regional and global levels. The World Council for Optometry is urged to provide leadership in this process by developing a Global Framework for Social Accountability in Optometric Education to guide regions and countries towards the adoption of social accountability. Key Words: optometric education; social accountability; World Council for Optometry; global framework; social determinants; eye care education.